Digitalisasi Hadis Ala Pusat Kajian Hadis (PKH): Distribusi, Ciri, dan Kontribusi dalam Kajian Hadis Indonesia - Suryadilaga, Muhammad Alfatih; Qudsy, Saifuddin Zuhri; Mustautina, Inayatul (Universitas Islam Negeri Imam Bonjol Padang, 2021)
PKH is a pesantren which is famous for digitizing hadith, which has unique characteristics and designs that make it different from other pesantren. By using interpretative approach, this study showed that through variety of hadith, creativity can be enjoyed by the wider community. At least through the PKH’s url that not only gives the hadith emphasis but also general science, digital products that can be enjoyed as well as highly enlightening videos from various religious teachers who are highly trusted both from within and outside the country. Students who conduct training at PKH are also able to make applications through Android, namely thematic design and others such as pdf books which can be enjoyed in general. This phenomenon is a natural phenomenon in the technological era and they are hadith experts capable of displaying traditions to be readable in society at large. Student works can be blessed at the playstore on the cellphone with the PKH keyword or Hadith Study Center.